Breeding status and aggressive communication in the Harlequin Duck Histrionicus histrionicus - Inglis, Ian R; Lazarus, John; Torrence, Rebecca L L F (Wildfowl, 2000)
The breeding behaviour of ducks reflects a number of conflicts, both between and within the sexes. While unpaired (single) birds attempt to obtain mates, already mated males may pursue the conflicting strategies of mate guarding and extra-pair courtship or copulation in order to sequester the mate while pursuing mating opportunities outside the pair bond. If females pursue the same strategies pair members will also be in conflict. We have sought to understand the nature of these complex interactions in the Harlequin Duck (Histrionicus histionicus), and in the present paper examine the conflict between paired and unpaired birds as it is manifest in agonistic encounters. Pairs are predicted by game theory models to dominate single males as a result of one or more competitive asymmetries and this prediction was supported, pairs both initiating and winning encounters against single males. Compared to pairs, single males were more likely to retreat and less likely to display back to an initiating display. Similarly, individuals were less likely to retreat in response to single male displays than to those of paired males or females. Displays in the order ’head nod away’, ’head nod at’ and ’extended neck’ were increasingly likely to result in a win. Responding birds tended to match the initiator’s display and males showed gradual escalation in their own displays. The greater use of ’extended neck’ by females probably reflected its use for inciting. Single males used more high intensity display (extended neck) and less low intensity display (head nod) against other single males than against pairs, in accord with the game theory prediction that encounters between closely-matched opponents will be of higher intensity. As a consequence of the dominance of pairs over single males the latter may find it impossible to obtain a mate on the breeding ground. This dominance, together with close mate guarding by both sexes, and female fidelity, is responsible for the rarity or absence of extra-pair copulations and mate switching, and the consequent strict monogamy found in this species.